Zatoichi: The Blind Swordsman Collection Based on Short Stories by Kan Shimozawa [Medienkombination] - Misumi, Kenji; Mori, Kazuo; Tanaka, Tokuzô; Yasuda, Kimiyoshi; Makiura, Chishi; Honda, Shôzô; Katsu, Shintaro (The Criterion Collection, 2019)
The colossally popular Zatoichi films make up the longest-running action series in Japanese history and created one of the screen's great heroes: An itinerant blind masseur who also happens to be a lightning-fast swordsman. As this iconic figure, the charismatic and earthy Shintarô Katsu became an instant superstar, lending a larger-than-life presence to the thrilling adventures of a man who lives staunchly by a code of honour and delivers justice in every town and village he enters. The films that feature him are variously pulse pounding, hilarious, stirring and completely off-the-wall. This deluxe set features the string of twenty-five Zatoichi films made between 1962 and 1973. [Cover]